2020
DOI: 10.1155/2020/4672340
|View full text |Cite
|
Sign up to set email alerts
|

Associations of Alpha and Beta Interhemispheric EEG Coherences with Indices of Attentional Control and Academic Performance

Abstract: Introduction. Heretofore, research on optimizing academic performance has suffered from an inability to translate what is known about an individual’s learning behaviors to how effectively they are able to use the critical nodes and hubs in their cerebral cortex for learning. A previous study from our laboratory suggests that lower theta-beta ratios (TBRs) measured by EEG may be associated with higher academic performance in a medical school curriculum. Methods. In this study, we tested the hypothesis that TBR … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…Alternatively, this complex pattern of positive and negative correlations between LLC and CRI may reflect differences in resting-state networks such as the DMN, dorsal attention network, and the frontoparietal network that have been previously shown to be anticorrelated in their activity ( Fox et al, 2005 ). These resting-state functional networks have been associated with the different frequency bands studied in this work (see Mantini et al, 2007 ; Hlinka et al, 2010 ; Neuner et al, 2014 ; Gorantla et al, 2020 ). Therefore, future studies potentially combining fMRI and EEG methods are needed to explore whether there is a dissociated pattern of relationships between those anticorrelated resting state networks and the observed EEG connectivity correlates of CR.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, this complex pattern of positive and negative correlations between LLC and CRI may reflect differences in resting-state networks such as the DMN, dorsal attention network, and the frontoparietal network that have been previously shown to be anticorrelated in their activity ( Fox et al, 2005 ). These resting-state functional networks have been associated with the different frequency bands studied in this work (see Mantini et al, 2007 ; Hlinka et al, 2010 ; Neuner et al, 2014 ; Gorantla et al, 2020 ). Therefore, future studies potentially combining fMRI and EEG methods are needed to explore whether there is a dissociated pattern of relationships between those anticorrelated resting state networks and the observed EEG connectivity correlates of CR.…”
Section: Discussionmentioning
confidence: 99%
“…All this complex pattern of correlations for LLC is reflecting the highly entangled networks among brain areas, probably showing differences in resting-state networks such as DMN, dorsal attention network, and the fronto-parietal network. Although, eyes-closed alpha activity has been considered the brain's default mode (Gorantla et al, 2020), Neuner et al (2014) found a strong link between the spontaneous BOLD response of different brain areas and the power of delta, beta 1 and beta 2. In addition, other studies have associated the activation of the DMN during resting-state with higher beta power in young adults (Hlinka et al 2010;Mantini et al, 2007).…”
Section: Correlational Analysismentioning
confidence: 99%
“…For example, a resting-state functional magnetic resonance imaging (fMRI) study indicated significant differences in the functional connectivity between EO and EC, mainly reflected in the thalamus’s amplitude modulation of low-frequency spontaneous activities of the sensory system ( Qian et al, 2019 ). One resting-state electroencephalogram (EEG) study found that there were significant differences in brain activities between eye states, mainly reflected in increasing α and β interhemispheric coherence with the EO state in frontal, temporal and occipital lobes ( Gorantla et al, 2020 ). Currently, the number of resting-state EEG studies has increased sharply.…”
Section: Introductionmentioning
confidence: 99%
“…Researchers often use time-domain and frequency-domain methods such as independent component analysis (ICA), EEG micro-state and low-frequency θ-β ratio to compare the brain neural activities of individuals with EO and EC during resting state ( Gorantla et al, 2020 ; Tamburro et al, 2021 ). In studies that directly compare the difference between EO and EC during resting state, EEG research accounts for a relatively small proportion.…”
Section: Introductionmentioning
confidence: 99%